2019
DOI: 10.1055/a-0743-5356
|View full text |Cite
|
Sign up to set email alerts
|

Rectal ultrasound with fine needle aspiration: an underutilized modality for delineating and diagnosing perirectal, presacral, and pelvic lesions

Abstract: Background and study aims  The merits of rectal ultrasound for rectal cancer staging are well documented. Conventional approaches to accessing perirectal and presacral lesions entail computed tomography guidance via a transgluteal approach or frank surgical exploration. We report on the safety and efficacy of performing rectal ultrasound with fine-needle aspiration (RUS-FNA) for evaluating perirectal, presacral, and pelvic abnormalities. Patients and methods  Patients who underwent RUS-FNA of perirectal, pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…Data on lower EUS for rectal and pelvic lesions are scant. Among the few studies that have reported on lower EUS adverse events, risks have been as high as 15 %–21 % 11 12 . Many participants, however, underwent other procedures concurrently with their lower EUS with fine-needle aspiration (FNA), including colonoscopy and polypectomy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Data on lower EUS for rectal and pelvic lesions are scant. Among the few studies that have reported on lower EUS adverse events, risks have been as high as 15 %–21 % 11 12 . Many participants, however, underwent other procedures concurrently with their lower EUS with fine-needle aspiration (FNA), including colonoscopy and polypectomy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Ainda que, a PAAF intra-retal seja pouco descrita em pequenos animais, e alguns autores afirmam que a citologia apresenta limitações para diagnóstico de tumores retais caninos [14], neste caso auxiliou na diferenciação da neoplasia enaltecendo sua aplicabilidade, mostrando-se de grande importância para o diagnóstico presuntivo e planejamento cirúrgico [15,17,20]. Em humanos, é reportado a utilização de PAAF guiada por UTR para coleta de amostras de massas de localização IP, sendo considerada ferramenta segura, precisa e útil para tomada de decisões, fornecendo diagnóstico eficaz em até 88% dos pacientes [5]. Em consonância, foi relatado a utilização de PAAF em cães com massas retais, e 4/5 exames foram consistentes com o diagnóstico definitivo [15].…”
Section: Discussionunclassified
“…Para a UTR, o animal foi submetido à medicação pré-anestésica [0,3 mg/kg IM de morfina (Dimorf @ ) 3 e 0,4 mg/kg IM de midazolam (Dormonid @ ) 4 ] e indução anestésica [4 mg/kg IV de propofol (Propovan @ ) 3 ]. A paciente foi mantida em plano anestésico [isoflurano (Isoforine @ ) 3 vaporizado em oxigênio à 100%] e fluidoterapia [ringer lactato 10 mL/kg/h IV], além de antibioticoprofilaxia [com 30 mg/kg IV de cefalotina sódica (Cefalotina sódica @ ) 5 ].…”
Section: Casounclassified